Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1212/wnl.46.6.1678
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate placebo-controlled dose-ranging trial in refractory partial epilepsy using 600-, 800-, and 1,000-mg daily dosages

Abstract: We conducted a multicenter, double-blind, randomized, parallel, placebo-controlled trial in 190 patients to evaluate the safety and efficacy of three dosages of topiramate (600, 800, and 1,000 mg/day) as adjunctive therapy for patients with refractory partial epilepsy. During an 18-week double-blind treatment period, median percent reductions from baseline in average monthly seizure rates were 1% for placebo, 41% for topiramate 600 mg/day and topiramate 800 mg/day, and 38% for topiramate 1,000 mg/day. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
152
1
11

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(175 citation statements)
references
References 4 publications
11
152
1
11
Order By: Relevance
“…One study 19 that compared placebo to 200, 400, and 600 mg/day showed a significant difference between the responder rate at 200 mg/day (27%) and 400 mg/day (49%), but the latter failed to differ with the responder rate at 600 mg/day (48%). The second study 20 confirmed this observation, as the responder rate at doses of 600, 800, and 1,000 mg/day failed to differ significantly, and these were similar to those reported at 400 mg/day in the previously cited study.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…One study 19 that compared placebo to 200, 400, and 600 mg/day showed a significant difference between the responder rate at 200 mg/day (27%) and 400 mg/day (49%), but the latter failed to differ with the responder rate at 600 mg/day (48%). The second study 20 confirmed this observation, as the responder rate at doses of 600, 800, and 1,000 mg/day failed to differ significantly, and these were similar to those reported at 400 mg/day in the previously cited study.…”
supporting
confidence: 84%
“…There were eight articles with class I evidence that assessed the efficacy of topiramate for refractory partial seizures as add-on therapy. [17][18][19][20][21][22][23][24] The target doses in these studies ranged between 200 mg/day and 800 mg/day. The 50% responder rate ranged from 27% at doses of 200 mg/day to 50.6% at mean doses of 450 mg/day.…”
mentioning
confidence: 99%
“…Five previous placebo-controlled, multicenter trials have shown TPM to be effective as add-on therapy for refractory partial onset seizures (10)(11)(12)(13)(14). The dosages evaluated in those trials ranged from 200 to 1,000 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…TPM appears to have multiple mechanisms of action that may include the following: reduction of epileptiform discharges and the number of action potentials (APs) produced in each discharge by blocking of voltagedependent Na+ channels ( 4 3 , enhancement of the activity of y-aminobutyrate (GABA) on GABA, receptors at a novel allosteric site (6)(7)(8), and antagonism of a glutamate-receptor subtype (9). Five clinical trials of TPM as adjunctive therapy with standard AEDs have demonstrated that the drug is effective for partial onset seizures with or without secondarily generalized tonic-clonic seizures in adult patients (10)(11)(12)(13)(14). The efficacy of TPM as adjunctive therapy suggested that the drug could be effective as monotherapy.…”
mentioning
confidence: 99%
“…Topiramate (TPM) is a broad-spectrum antiepileptic drug (AED) used as adjunctive and monotherapy (1)(2)(3)(4). It is one of the most powerful of the new AEDs, effective in a wide variety of seizure types (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%